Estratégias de busca por assunto no Sistema Único de Informação: estudo com os usuários internos da Procuradoria da República nos Estados da Paraíba, Rio Grande do Norte e Pernambuco - Patrício, Rebeca de Oliveira (2019)
In this work, I study issues related to Information Retrieval, Information Representation and Information Users. I have as general objective to analyze the strategies of search by subject used by the internal users at the Attorney General’s Office of the Republic in the states of Paraiba, Rio Grande do Norte and Pernambuco in the Single System of Information for the purpose of recovering the civil and criminal court documents. I specifically aim to describe the functionalities of the Single System of Information regarding the activity of searching by subject for the purpose of recovering these court documents; to identify the search by subject strategies that the internal users of the Attorney General's Office in the State of Paraiba, Rio Grande do Norte and Pernambuco use for the recovery of court documents in this system; to verify if users associate their strategies with the table of subjects in the activity of searching court documents. I used the bibliographical and descriptive research with a qualitative approach as methodology, being the theoretical reference constituted by the literature of Information Science. As a data collection instrument, I used a semi-structured questionnaire developed in the light of the alternative approach of user studies and applied with workers of the Attorney General’s Office of the Republic in the Civil and Criminal Nuclei and of the Citizen and User Assistance Section. I show that although the organ contains a controlled vocabulary, the subjects that participate in the research, for the most part, use natural language as the main strategy for searching and retrieving documents. I have identified that users commonly associate a search behavior as ideal by using it repeatedly, even if the demand or situation is different. I conclude by presenting proposals for improvements to the Single System and strategies that can have a positive impact on the retrieval of documents in this context.